A novel iterative method for solving chemical kinetics system - Chowdhury, Md. Sazzad Hossien; Ghosh, Indranil; Mt Aznam, Suazlan; Mawa, Shukranul (2021)
The purpose of this research is to impose a semi-analytical method called the Iterative Method (IM) to the chemical kinetics system, which appears in the form of a system of Ordinary Differential Equations (ODEs). To test the accuracy of the standard IM, we have applied the classical fourth-order Runge-Kutta method (RK4) and the IM to the chemical kinetics system. It is significantly notable that, approximate analytical precisions of standard IM made a high agreement with those obtained from the RK4 technique. Numerical outputs and solution procedures indicate that IM can be easily applicable to a large class of scientific numeric applications with high accuracy.